KOMITMEN ORGANISASI SEBAGAI PEMMODERASI HUBUNGAN PARTISIPASI ANGGARAN DENGAN SENJANGAN ANGGARAN (Studi Empiris Perusahaan Jasa Perhotelan Kota Magelang) - Zuhriyah, Eny (Universitas Muhammadiyah Magelang, 2007)
The research was aimed at evaluating empirically the effects of budgeting participation on the budgeting unbalance and the effects organization commitment on the relationship between budgeting participation and budgeting unbalance. The data gained were primary; the samples were taken by means of a purposive sampling technique in which the midlevel managers from 16 Hotel Companies in Magelang fulfilled the questionnaires given. 64 questionnaires were distributed and 36 were processed. The data were analyzed by applying Moderating Regression Analysis. Prior to the subsequent data processing, normality test, validity test, and reability test were conducted. The contribution of independent variables on dependent ones is indicated by determination coefficient test (R2 rest). t test and F test were applied to evaluate the hypothesis. The results show positive relationship between budgeting participation and budgeting unbalance; negative relationship between organization commitment and budgeting unbalance; and positive relationship between interaction of budgeting participation with organization commitment and budgeting unbalance. The reearch is more influenced by the other variables excluded in the study. Considering the results, it is suggested to add the variables influencing budgeting unbalance in spite of those included in this inquiry, such as, information asymmetry, leadership style, and managerial performance.